2017
DOI: 10.24875/ric.17002152
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NRAMP1/SLC11A1 Gene Variant D543N (1730G/A) in the Genetic Susceptibility to Develop Rheumatoid Arthritis in the Mexican Mestizo population

Abstract: background:Rheumatoid arthritis is a chronic inflammatory disease whose cause has not been fully elucidated. However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This twofold activity, which reflects polarization of MF phenotypes along the spectrum of M1 to M0 to M2 states, may contribute to the complexity in NRAMP1 activation, by analogy with different profiles of enhancer activation reported in Th1 vs. Th2 lymphocytes [20], even though mechanisms that differentiate Th cell subsets are not governed by combinations of lineage- and stimulus-dependent TFs such as those described in MFs [22,196]. In turn, complex regulation of NRAMP1 expression may partly explain how SNPs may be associated with susceptibility to infections and/or autoimmune diseases in different human populations [111,197,198,199,200]. …”
Section: Discussionmentioning
confidence: 99%
“…This twofold activity, which reflects polarization of MF phenotypes along the spectrum of M1 to M0 to M2 states, may contribute to the complexity in NRAMP1 activation, by analogy with different profiles of enhancer activation reported in Th1 vs. Th2 lymphocytes [20], even though mechanisms that differentiate Th cell subsets are not governed by combinations of lineage- and stimulus-dependent TFs such as those described in MFs [22,196]. In turn, complex regulation of NRAMP1 expression may partly explain how SNPs may be associated with susceptibility to infections and/or autoimmune diseases in different human populations [111,197,198,199,200]. …”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure , a total of 77 studies were identified by searching PubMed, CNKI, and Web of Science databases systemically and holistically. After excluding 17 repetitions, one data redundancy, 34 non‐RA, three non‐human, seven reviews, two meta‐analyses, four family genetics and two with data unavailable, five articles with available data matched the inclusion criteria and were enrolled in this meta‐analysis. However, one of these only had data on common homozygous carriers and the sum of heterozygote and rare homozygous carriers.…”
Section: Resultsmentioning
confidence: 99%
“…The variant was not only associated with TB but also was implicated in other diseases as well. The rs17235409 variant was among the list of host factors associated with susceptibility to leishmaniasis ( Ates et al, 2009 ) and rheumatoid arthritis ( Niño-Moreno et al, 2017 ; Braliou et al, 2019 ). Our analysis shows that rs17235409 might be a promotor/repression gene mutation, which could lead to significant phenotypic consequences.…”
Section: Discussionmentioning
confidence: 99%